Animation principles in multimedia learning - Lowe, Ric; Schnotz, W. (2014)
This chapter describes a set of principles to be considered in the design of animation for use in multimedia learning resources. It then presents examples of some applications of these principles. The animation principles are grounded in research on perception, cognition and instruction, culminating in an account of the Animation Processing Model (APM). Animation in multimedia learning environments has multiple facets and can serve multiple functions. Dynamic perceptual schemata play a crucial role in the recognition of movement. The APM characterizes learning from animation in terms of five main phases in which bottom-up and top-down processes interact during the construction of a mental model that internally represents the referent subject matter. Learning from animation in multimedia learning environments raises important questions for cognitive theory with respect to visualization because it requires special attention to the interface between perception and cognition. The chapter also discusses implications for instructional design.